2019
DOI: 10.22336/rjo.2019.56
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of effective orbital volume and its association with axial length of the eye. A 3D-MRI study

Abstract: Objective: To measure the effective orbital volume (EOV) from magnetic resonance images, and investigate its relationship with axial length (AL) in those parameters. Methods: Cross-sectional, 3D-MRI study. 54 eyes of 54 patients (25 males) were included in this work. Patient weight, height and head circumference were also measured. Orbital and eyeball volumes were calculated after image segmentation. The difference between those values volume was assessed, estimating the EOV for each eye. Results: Mean eyeball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…Bontzos et al demonstrated that normal orbital volume was significantly correlated with axis length 25 . Our work found a positive linear correlation between orbital volume and axis length in the affected and unaffected eyes.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Bontzos et al demonstrated that normal orbital volume was significantly correlated with axis length 25 . Our work found a positive linear correlation between orbital volume and axis length in the affected and unaffected eyes.…”
Section: Discussionsupporting
confidence: 73%
“…Bontzos et al demonstrated that normal orbital volume was significantly correlated with axis length. 25 Our work found a positive linear correlation between orbital volume and axis length in the affected and unaffected eyes. The results of our predictive modeling indicated that every 1 mm change in axis length caused a 0.38 cm 3 change in orbital volume in the affected group and a 0.73 cm 3 change in the unaffected group.…”
Section: Correlation Between Orbital Volume and Axis Lengthsupporting
confidence: 51%
“…Our findings confirm a relation between smaller AL and more asymmetrical orbits, with mild cases not affecting orbital symmetry and voluminous intra‐orbital cysts causing a strikingly larger orbit. The relationship between AL and orbital volume has repeatedly been established (Bontzos et al., 2019; Yang et al., 2012; Ye et al., 2022). We observed more orbital asymmetry in cases with eyes smaller than 10.5 mm.…”
Section: Discussionmentioning
confidence: 96%
“…These ambiguous results might be explained by the broad variety of methodologies used to measure and process orbital volumes. Moreover, in these small study populations, the inter-individual and intra-individual differences in orbital volume, as well as the differences in orbital volume between the sexes (20-32 ml, 2.5-4.1%, and around 8%, respectively) may also be of importance 39,[51][52][53] . This is especially the case, since the mean range of the orbital volume difference between the injured and uninjured orbits is 1.4-5.7 ml, which is around 5-21% (using a mean orbital volume of 27 ml) 27,28,38,39 .…”
Section: Orbital Volumementioning
confidence: 99%